The impact of demand deposit, saving deposit, time deposit, deposits from other banks, and equity toward loans of pt bank windu kentjana international tbk. (for the period of quarter ii 2008 â€“ quarter i 2016) - Winarno, Matius; K. Widhaningrat, Sisdjiatmo (The Indonesian Journal of Business Administration, 2016)
Abstract - The focus of this study is analyzing the impact of demand deposit, saving deposits, time deposits as the third party fund components, fund borrowings, deposits from other bank as the second party fund component, and equities as the first party fund component, towards the loan of PT Bank Windu Kentjana International Tbk. This final project was using quantitative approach. An explanatory type of research was chosen to be in line with the research. Using multiple regression model. The data analyzed with ordinary least square (OLS) method. This research suggest, that PT Bank Windu Kentjana International Tbk. should raise the balance of demand deposits and saving deposits in order to be significant sources of fund for loan. Hopefully, PT Bank Windu Kentjana International Tbk. will be able to diversify its deposits by raising other third party fund component beside of time deposit, considering that funds from demand deposit and saving deposit product are low-cost source of fund which could be act as potential contributor for loans.Â Key words: Bank, Loan, Asset and Liability Management.